The Prevision of Public Inputs in Oligopolitic Markets - Gianluca Fiorentini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
Optimal rules for the provision of collective factor of production have been quite extensively investigated since the seminal cotributions of Kaizuka (1965) and Sandro (1972), that may be regarded as the counterpart of the Samuelson's papers on the optimal allocation of public goods amoung consumers.
Keywords: 330